Business mathematics the easy way - Goozner, Calman (New York : Barron's, 1991)
Covers such aspects of business mathematics as basic arithmetic, statistics, measurements, and personal finance.
Includes index.
Keywords: Business mathematics; Business mathematics; Mathematics